Molecular and phenotypic data reveal a new Amazonian species of pit vipers (Serpentes: Viperidae: Bothrops). Issue 37 (1st October 2020) - Dal Vechio, Francisco; Prates, Ivan; Grazziotin, Felipe G.; Graboski, Roberta; Rodrigues, Miguel Trefaut
ABSTRACT: Recent genetic studies have found unclear species boundaries and evidence of undescribed diversity in the poorly studied jararacussu species group within Bothrops . In this contribution, we investigate phenotypic and genetic diversity in the Amazonian snake Bothrops brazili to test previous assertions of unrecognised species diversity within this taxon. Our phylogenetic results and inferences of independently evolving lineages based on molecular data recover two divergent clades within B. brazili, one restricted to areas north and another to areas south of the Amazon River. Phylogenetic relationships between these lineages and other species in the jararacussu species group reveal B. brazili to be paraphyletic, with the northern clade inferred as sister to a clade composed of Atlantic Forest taxa ( B. jararacussu, B. muriciensis, B. pirajai ). External morphology (number of ventral and subcaudal scales) and colouration patterns (lateral trapezoidal marks) consistently separate the two lineages of B. brazili . We therefore recognise and describe the northern lineage as a new species of Bothrops, improving our knowledge of species diversity within a medically important clade of venomous South American snakes.